2010
DOI: 10.1007/s10533-010-9451-4
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and hydrologic drivers of dissolved organic matter and nutrients in the upper Kuparuk River, Alaskan Arctic

Abstract: As the planet warms, widespread changes in Arctic hydrology and biogeochemistry have been documented and these changes are expected to accelerate in the future. Improved understanding of the behavior of water-borne constituents in Arctic rivers with varying hydrologic conditions, including seasonal variations in discharge-concentration relationships, will improve our ability to anticipate future changes in biogeochemical budgets due to changing hydrology. We studied the relationship between seasonal water disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 73 publications
(104 reference statements)
5
50
1
Order By: Relevance
“…In 2007, prior to disturbance, the two catchments exhibited very similar concentrations and seasonal patterns in the different N components (NH 4 + , NO 3 − , DON), with DON accounting for more than 90% of the TDN flux, which is similar to that reported for the larger rivers at Cape Bounty (Lafrenière and Lamoureux 2008;Lewis et al 2012) as well as for other Arctic rivers (McNamara et al 2008;Townsend-Small et al 2011). The only notable differences between the two catchments prior to disturbance were the higher mean nival period NH 4 + concentration (~3 times higher) and lower seasonal mean NO 3 − in GS.…”
Section: Predisturbance Conditionssupporting
confidence: 73%
See 1 more Smart Citation
“…In 2007, prior to disturbance, the two catchments exhibited very similar concentrations and seasonal patterns in the different N components (NH 4 + , NO 3 − , DON), with DON accounting for more than 90% of the TDN flux, which is similar to that reported for the larger rivers at Cape Bounty (Lafrenière and Lamoureux 2008;Lewis et al 2012) as well as for other Arctic rivers (McNamara et al 2008;Townsend-Small et al 2011). The only notable differences between the two catchments prior to disturbance were the higher mean nival period NH 4 + concentration (~3 times higher) and lower seasonal mean NO 3 − in GS.…”
Section: Predisturbance Conditionssupporting
confidence: 73%
“…In continuous permafrost catchments, these factors are tightly linked: permafrost confines runoff and biological activity to the active layer and hydrologic processes exert a strong control on nutrient export dynamics (MacLean et al 1999;Stieglitz et al 2003;Townsend-Small et al 2011;Yano et al 2010;Harms and Jones 2012;Koch et al 2013;Harms and Ludwig 2016). The timing of TDN flux depends largely on runoff volume and the response to hydrological inputs in a catchment.…”
Section: Introductionmentioning
confidence: 99%
“…Solutes are generally supply limited and hence continued mobilization is necessary to sustain fluxes in surface water. Previous research has suggested that, next to snowmelt, rainfall is a major water source capable of generating biogeochemical fluxes in Arctic nival catchments (Everett et al 1989;Judd and Kling 2002;McNamara et al 2008;Townsend-Small et al 2011). The major rainfall event (>25 mm day) in July 2009 and above-average total rainfall in July 2012 at CBAWO provided sufficient water for ion mobilization, resulting in a sharp increase in TDS concentrations in PT runoff in mid-July (Fig.…”
Section: Impacts Of Physical Disturbance On Hydrochemistrymentioning
confidence: 92%
“…For example, warming is increasing the density of shrub vegetation, which traps more snow (Pomeroy et al 2006). This leads to greater snowmelt input (Turner et al 2010(Turner et al , 2014 and increased supply of allochthonous nutrients (e.g., nitrogen and phosphorus) and dissolved organic carbon (DOC) to downstream lakes and rivers (Finlay et al 2006;Townsend-Small et al 2011;Lapierre et al 2015). Increased lake-water concentrations of nutrients and DOC have also been associated with climate warming, via stimulation of terrestrial production and microbial decomposition within the catchment, and release of elements from previously frozen ground (Frey and Smith 2005).…”
Section: Introductionmentioning
confidence: 99%